Understanding personal, social, health and economic education in secondary schools - McWhirter, Jenny; Boddington, Nick; Barksfield, Jenny (SAGE Publications Ltd, 2017)
This book provides an overview essential for a proper understanding of effective approaches to PSHE education in secondary education and the valuable role it can play in promoting the health and wellbeing of adolescents. Coverage includes: . The importance and scope of PSHE education . The theory and research evidence for effective practice in the secondary school . School structures which support effective teaching and learning in PSHE education . Assessment for, and of, learning in PSHE education . The role of visiting experts in PSHE education . Overlaps with pastoral and therapeutic support